The Effect of Gargling with Peppermint Water on Thirsty in CKD (Chronic Kidney Disease) Undergoing Hemodialysis At Harapan dan Doa Hospital 2023 - Nurfadilla, Rahmi; Hermansyah, Hermansyah; Septiyanti, Septiyanti; Gregorio, Joem Oliveros (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: Chronic kidney disease is a condition in which the body is unable to maintain balance in metabolism, fluids, and electrolytes due to irreparable damage to kidney function. One of the problems that can occur in hemodialysis patients is thirst. Therefore, it is important to treat thirst. Gargling with peppermint water is one way to quench thirst and overcome it.Objective: The purpose of this study was to find out whether gargling with peppermint water is effective in reducing thirst in kidney failure patients undergoing hemodialysis at Harapan dan Doa Hospital Bengkulu.Method: This study used quasi-experimental methods. The population in this study is 65 patients suffering from chronic kidney failure and undergoing hemodialysis at Harapan dan Doa Hospital in Bengkulu City. The total sample of this study amounted to 36 people who followed the treatment in Harapan dan Doa Hospital Bengkulu, which were divided into two groups, namely the intervention group of 18 people and the control group of 18 people. A purposive sampling technique was used in this study. In addition, visual analog scale instruments for assessing thirst were used as questionnaires to assess thirst.Result: The study showed that there was a difference in average thirst sensation between the intervention groups and the control group. For the Mann-Whitney statistical test for thirst, the p-value was 0.026 (p-value ≤ α 0.05). This suggested that gargling with peppermint water affected thirst in hemodialysis patients.Conclusion: Hence peppermint water gargle therapy may be recommended as a non-drug treatment to control taste thirst in renal failure patients undergoing hemodialysis.